Intercropping systems and soil amendments under long-term no-till on phosphorus dynamics - Vilela, Rafael Gonçalves [UNESP] (Universidade Estadual Paulista (Unesp), 2023)
The management of weathered tropical soils, with low availability of phosphorus and the presence of a dry season in winter, is a challenge to favor the levels of organic matter and improve the efficiency of phosphate fertilization. Intercropping maize second crop with cover crops has improved soil quality, enhancing the input of straw in the production system, favoring nutrient cycling and efficient use of natural resources by commercial crops, increasing productivity. The effects of intercropping systems on off-season (autumn-winter) cropping and changes in soil acidity on soil P dynamics were evaluated in a randomized block experiment in split plots. The single or intercropped maize cultivation system with signal grass + sunn hemp were considered as the main plots, and the acidity correction through silicate, limestone or without correction were treated as subdivided plots. Soy is grown as a main crop in the summer seasons. The intercropping of maize in the off-season increases the yield of maize and soybeans by approximately 30 and 9%, respectively. The greater input of plant residues through intercropping temporarily reduces the lability of Po and Pi in the soil at 0-0.05 m depth, but does not limit P uptake by crops. Liming, regardless of the corrective used, increases the pool of Pi in the soil, specifically for labile forms due to the release of P linked to Al and Fe. Intercropping maize second crop with Brachiára and Sunn hemp is a good option for plant diversification in the area, increasing land use efficiency and SP sustainability in tropical agriculture, providing higher yields compared to the monoculture system.

O manejo de solos tropicais intemperizados, com baixa disponibilidade de fósforo e presença de uma estação seca no inverno, é um desafio para favorecer os índices de matéria orgânica e melhorar a eficiência das adubações fosfatadas. O consórcio do milho segunda safra com plantas de cobertura tem melhorado a qualidade dos solos, potencializando o aporte de palhada no sistema de produção, favorecendo a ciclagem de nutrientes e eficiência no uso dos recursos naturais pelas culturas comerciais, aumentando a produtividade. Os efeitos de sistemas de cultivo consorciados na cultura de entressafra (outono-inverno) e as alterações da acidez do solo sobre a dinâmica de P no solo foram avaliadas em um experimento de blocos ao acaso em parcelas subdivididas. Sendo o sistema de cultivo milho solteiro ou consorciado com capim braquiária + crotalária considerados como as parcelas principais, e a correção de acidez através do silicato, calcário ou sem correção foram tratados como parcelas subdivididas. A soja é cultivada como cultura principal nas estações de verão. O cultivo consorciado de milho na entressafra aumenta em cerca de 30 e 9% o rendimento das culturas de milho e soja respectivamente. O maior aporte de resíduos vegetais através da consorciação reduz temporariamente a labilidade de Po e Pi do solo a 0-0,05 m de profundidade, más não limita a absorção de P pelas culturas. A calagem independente do corretivo utilizado, aumenta o pool de Pi do solo, especificamente para formas lábeis em decorrência a liberação de P ligado a Al e Fe. O consórcio de milho segunda safra com braquiára e crotalária é uma boa opção para diversificação de plantas na área, aumentando a eficiência do uso da terra e a sustentabilidade do SP na agricultura tropical, proporcionando maiores produtividades em comparação com o sistema monocultivo.
Sistemas de culturas intercalares e corretivos do solo em regime de plantio direto de longa duração na dinâmica do fósforo
Keywords: resíduos vegetais; silicato; braquiária; milho; fósforo orgânico do solo; crop straw inputs; silicate; ruzigrass; maize; soil organic phosphorus